Adolescents and long-acting reversible contraceptives: beyond the basics. Issue 6 (December 2020) - Stanton, Taylor; Cizek, Stephanie; Tyson, Nichole
Abstract : Purpose of review: The current article explores some of the more complex subtopics concerning adolescents and long-acting reversible contraceptives (LARC). Recent findings: Recent research has highlighted ways in which LARC provision can be optimized in adolescents and has identified gaps in adolescent LARC access and utilization. Summary: Contraceptive counseling for adolescents should be patient-centered, not necessarily LARC-first, to avoid coercion. There are increasing applications for the noncontraceptive benefits of LARC for several unique patient populations and medical conditions.